Field hockey sport-specific postures during unanticipated sidestepping: Implications for anterior cruciate ligament injury prevention - Smith, M.; Weir, G.; Donnelly, C. J.; Alderson, J. (Journal of Sports Sciences, 2020)
Much research has investigated whole-body postures and associated knee joint loading during unanticipated sidestepping (UnSS). However, no research has considered sport-specific postures in field hockey. The purpose of this study was to investigate differences in trunk and lower limb angle and lower extremity joint moment waveforms during UnSS while holding a hockey stick in a flexed posture (HS-UnSS) and traditional UnSS. Additionally, we aimed to determine if differences in posture during HS-UnSS were associated with changes in knee joint moments. Twelve elite female field hockey athletes underwent 3D motion analysis during UnSS and HS-UnSS. Athletes increased trunk (0-100% of stance phase, hip (0-15%), knee (12-29%; 39-59%; 78-100%) and ankle (41-57%) flexion angles, and increased hip flexion (19-24%; 42-45%; 75-84%) and external rotation moments (75-80%) during HS-UnSS compared with UnSS (p < 0.05). Flexed postures observed during HS-UnSS did not influence knee flexion and valgus moments when compared with UnSS (p > 0.05), however knee external rotation moments reduced. Changes in trunk flexion were positively associated with peak knee internal rotation moments from UnSS to HS-UnSS (r = 0.779, p = 0.005). These findings indicate that field hockey players sidestep with significantly different techniques when holding a hockey stick, which should be considered in injury prevention training protocols.